Optical bistability in all-pass mobius configuration microring resonator - Noorden, Ahmad Fakhrurrazi Ahmad; Bahadoran, Mahdi; Chaudhary, Kashif; Aziz, Muhammad Safwan; Jalil, Muhammad Arif; Ali, Jalil; Yupapin, Preecha (My University, 2015)
A novel design of microring resonator called all-pass Mobius ring resonator is used to study optical bistability effect and spectral transmission for all-optical switching application with clockwise hysteresis loop operation. The bright soliton pulse is applied as the input source of the system. The propagation of the pulses within the system is simulated using the transfer matrix analysis. The all-pass Mobius ring resonator is able to operate under high nonlinearity as it has longer propagation length per roundtrip. The all-pass Mobius provides low transmission peak power of 3.65 mW as compared to the conventional all-pass configuration. The output-to-input relation of both design shows that the Mobius configuration is able to generate a higher hysteresis loop width of the bistable signal from 15.79 mW to 18.10 mW input power. The switching power of the optical bistability in Mobius configuration is 3.67 mW for threshold power of 16.95mW. This work shows the Mobius configuration is more suitable to be used for all-optical switching application as compared to the conventional all-pass ring resonator configuration.
Keywords: Hysteresis loop; Mobius ring resonator; Optical bistability; Transfer matrix